Study on Strength and Durability Characteristics of Concrete Containing Rice Straw ASH and Foundry Sand (International Journal of Innovative Research in Engineering & Management, 2022)
The production of raw cement results in  carbon emissions into the environment which is a serious  agenda that needs to be solved quickly before it's too late for  the environment. Almost 8% of total carbon emissions from  all over the world come from the cement industry. Billions  of tons of carbon dioxide gas are being released into the  environment when cement is produced in the manufacturing  plants which are damaging the ozone layer of the earth. An  alternative solution to the problem may be the use of  sustainable concrete prepared by replacing some portion of  cement with agro-industrial waste materials such as rice  straw ash, foundry sand, rice husk ash etc. In the present study, use of rice straw ash and foundry sand as partial  replacement of cement and fine aggregate has been  investigated. The sustainable concrete of M35 grade using  rice straw ash (5%, 10%, 15% and 20%) and foundry sand  (5%, 10%, 15% and 20%) by partial replacement of cement  has been prepared and various properties of concrete have  been investigated.
Keywords: Sustainable Concrete; Rice Straw Ash; Foundry Sand